12.9k views
2 votes
For f(x)=3x+1 and g(x)=(x^2)-6, find (f+g)(x).

2 Answers

4 votes

Answer:
(f+g)(x)=x^2+3x-5.

Step-by-step explanation: We are given the following two functions :


f(x)=3x+1,\\\\g(x)=x^2-6.

We are to find the value of (f + g)(x).

We know that

for any two functions p(x) and q(x),


(p+q)(x)=p(x)+q(x).

Therefore, we get


(f+g)(x)\\\\=f(x)+g(x)\\\\=(3x+1)+(x^2-6)\\\\=3x+1+x^2-6\\\\=x^2+3x-5.

Thus,
(f+g)(x)=x^2+3x-5.

User Ramineni Ravi Teja
by
5.4k points
3 votes


f(x)=3x+1;\ g(x)=x^2-6\\\\(f+g)(x)=(3x+1)+(x^266)=3x+1+x^2-6=x^2+3x+(1-6)\\\\=\boxed{x^2+3x-5}

User CrazyPen
by
5.4k points